Lubimec publiki ili mišen' dla kritikov: vospriatie tvorčestva Ežena Su v Rossii v XIX veke = Readers` favourite or critics` punch ball ? The reception of Eugene Sue`s works in Russia - Urban-Podolan, Aleksandra (1974- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article offers an overview of Russian translations of Eugene Sue`s works which came out in hislifetime and the main modes of their reception in Russia. Special attention is paid to their critical assessment by the most popular Russian magazines of the 1830?s and 1840`s ("Biblioteka dla tchtenia" - "Reader`s Library", "Otechestvennye Zapiski" - "Annals of the Fatherland", "Teleskop" - "Telescope", and others) and by Vissaryon Grigoryevich Belinsky (1811-1848), one of the most eminent Russian thinkers of the time, who devoted most of his work as a literary critic to Sue`s novels - from his first published essay "Literaturnye Metshtaniya" ("Literary Reviews", 1834) till the last years of his life.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); krytyka literacka rosyjska; 19 w.